2008
DOI: 10.1016/j.bbr.2008.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the benefits of caffeine, naps and placebo on verbal, motor and perceptual memory

Abstract: Caffeine, the world's most common psychoactive substance, is used by approximately 90% of North Americans everyday. Little is known, however, about its benefits for memory. Napping has been shown to increase alertness and promote learning on some memory tasks. We directly compared caffeine (200mg) with napping (60-90 minutes) and placebo on three distinct memory processes: declarative verbal memory, procedural motor skills, and perceptual learning. In the verbal task, recall and recognition for unassociated wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 51 publications
5
89
0
3
Order By: Relevance
“…While controlling for circadian effects, the present study found that sleep specifically enhanced the associative network for primed solutions but did not improve memory consolidation. Although other studies have reported that sleep enhances explicit verbal memory (22,35), our memory measures were not comparable with these recall tasks because exposure to the verbal material was primed and not explicitly presented. Furthermore, not only were NREM sleep, REM sleep, and quiet rest groups indistinguishable on the memory measures, performance on these memory measures was not correlated with performance on the primed RAT items.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…While controlling for circadian effects, the present study found that sleep specifically enhanced the associative network for primed solutions but did not improve memory consolidation. Although other studies have reported that sleep enhances explicit verbal memory (22,35), our memory measures were not comparable with these recall tasks because exposure to the verbal material was primed and not explicitly presented. Furthermore, not only were NREM sleep, REM sleep, and quiet rest groups indistinguishable on the memory measures, performance on these memory measures was not correlated with performance on the primed RAT items.…”
Section: Discussionmentioning
confidence: 74%
“…Because daytime sleep has been shown to increase alertness and improve a range of cognitive functions (perceptual, verbal, and motor learning; declarative and implicit memory) (18,(21)(22)(23)(24), we tested whether sleep or quiet rest might enhance general creativity on new RAT items. Baseline assessments were measured on the morning RAT.…”
Section: Figmentioning
confidence: 99%
“…The Karolinska sleepiness scale (KSS) was administered as a measure of subjective feelings of sleepiness/alertness (1 = very alert, 9 = very sleepy) (Akerstedt and Gillberg, 1990), with demonstrated sensitivity to caffeine effects (Mednick et al, 2008). The Dutch short visual analogue scale (VAS) version of the Profile of Mood States (POMS) (Wald and Mellenbergh, 1990) was administered; the fatigue (6 items: 0 = low fatigue, 100 = high fatigue) and vigour (5 items: 0 = low vigour, 100 = high vigour) subscales are recommended measures of the mood of energy and fatigue in investigations that are short in duration (O'Connor, 2006) and the vigour scale has shown sensitivity to caffeine effects (Childs and de Wit, 2008;Herz, 1999).…”
Section: Subjective Rating Scalesmentioning
confidence: 99%
“…A growing body of literature in areas outside of health care supports the concept that vigilance 45 and memory 46,47 are improved when workers are allowed to nap. Several studies support positive outcomes for on-duty napping by health professionals.…”
Section: Benefits Of Night Shift Nappingmentioning
confidence: 99%